GARAP ROG-ROG ASEM DALAM GENDING GAYA SURAKARTA - Sugimin Sugimin; Eko Nopi Astuti (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractGarap Rog-rog Asem is a kind of garap (treatment or interpretation) which accentuates the treatment of dynamics, in terms of irama, tempo, and volume, and with the use of andhegan. The performance of garap Rog-rog Asem is formed by a number of different elements, such as the form of gendhing, garap ricikan (treatment of the different instruments), treatment of dynamics, and treatment of the vocal melody. In general, garap Rog-rog Asem is performed in gending sekar in the form of ketawang, in which the main melody contains balungan plesedan and or balungan nggantung, such as Ketawang Sinom, Ketawang Kinanthi Sandhung, and Ketawang Gambuh. The most prominent treatment of the instruments in garap Rog-rog Asem is the treatment of the kendhang, balungan, and structural instruments. The function of the kendhang is to give signs (ater) using specific patterns and kendhangan pematut. The play on dynamics by the balungan instruments in garap Rog-rog Asem is to use balungan plesedan and or balungan nggantung which is developed to become balungan ngracik performed in a fast tempo and with a loud volume. The function of the structural instruments in garap Rog-rog Asem is to play like in the form of srepeg. These different elements combine to form a musical interaction and create a unity of garap known as garap Rog-rog Asem. A number of factors that highlight garap Rog-rog Asem include the interpretation of garap, differences in function, and the creativity of the artists. In addition to its use in klenengan, garap Rog-rog Asem is also often used in karawitan tari (dance accompaniment), karawitan pakeliran (accompaniment for shadow puppet theatre), and karawitan kethoprak (accompaniment for traditional stage dramas). It is believed that garap Rog-rog Asem was originally used for the accompaniment of dance.  Keywords: Rog-rog Asem, dynamic play, and gending sekar. AbstrakGarap Rog-rog Asem adalah garap yang menonjolkan garap dinamik, baik irama, tempo sajian, maupun volume tabuhan dengan menggunakan andhegan. Sajian garap Rog-rog Asem dibentuk oleh beberapa unsur yaitu bentuk gendhing, garap ricikan, garap dinamik, dan garap vokal. Garap Rog-rog Asem pada umumnya   disajikan pada gending sekar bentuk ketawang yang pada bagian lagu pokoknya terdapat balungan plesedan dan atau balungan nggantung, seperti Ketawang Sinom, Ketawang Kinanthi Sandhung, dan Ketawang Gambuh. Sementara garap ricikan yang menonjol dalam garap Rog-rog Asem adalah ricikan kendhang, ricikan balungan, dan ricikan struktural.  Ricikan kendhang berfungsi untuk memberi tanda atau ater dengan pola-pola tertentu dengan  menggunakan pola kendhangan pematut. Permainan dinamik yang dilakukan oleh ricikan balungan dalam garap Rog-rog Asem adalah menggarap balungan plesedan dan atau balungan nggantung yang dikembangkan menjadi balungan ngracik yang disajikan dengan tempo cepat serta volume yang keras. Sementara fungsi ricikan struktural dalam garap Rog-rog Asem adalah menyajikan garapan seperti bentuk srepeg. Berbagai unsur tersebut bekerja secara bersamaan sehingga membentuk suatu interaksi musikal dan menjadi kesatuan garap yang disebut dengan garap Rog-rog Asem. Beberapa faktor yang  memunculkan garap Rog-rog Asem, di antaranya adalah tafsir garap, perbedaan fungsi, dan kreativitas seniman. Selain disajikan dalam acara klenengan, garap Rog-rog Asem juga sering digunakan sebagai karawitan tari, karawitan pakeliran, dan karawitan kethoprak. Terdapat dugaan bahwa  garap Rog-rog Asem pada mulanya digunakan untuk keperluan karawitan  tari.Kata kunci: Rog-rog Asem, permainan dinamik, dan gending sekar.